Designing structures based on sensory and creative approach a case study on applying sensory intensification - Quiblat, Rossa Katrina B. (2011)
The retinal-bias architecture of our time is clearly giving rise to a quest for a sensory intensified architecture, more architects of our time has realized the bias and thus slowly trying to take into consideration the other senses that has been deprived. The research studied the reactions of respondents in an art installation space through narratives and cognitive maps. The narrative is the primary tool used to know and associate artworks, settings arrangement and space relations of one person compared to another. The research showed that architecture has truly embraced the architecture of the eye as shown in the variables in the Haptic experience. Kinesthetic experience and Synaesthetic experience that the respondents have taken into consideration while investigating the space they are in. the cognitive map was used to correlate the factors written down on the narratives. Hapticity pertaining to what is heard, seen, touched, smelled and felt, Kinesthetic experience or the association of feelings towards materials and interaction to space and Synaesthetic experience the physical interaction to environment are main concepts embraced by sensory intensification. These are the core components that needs to be prioritize in designing structures especially iconic, monumental, art installation areas and museum buildings. There is a need to create a place which will instill lasting memory such that a strong image of Davao can be embedded to the minds of the locals and visitors alike. This study focused on Davao City a haven of rich variation of arts and local inspiration, a character which could easily arouse interest and curiosity.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2011